The West African Economic and Monetary Union : Recent Developments and Policy Issues - Hernandez-Cata, Ernesto (Occasional Papers; Occasional Paper ;, 1998)
Following a serious deterioration of the competitive position of the WAEMU region in the 1980s and the eary 1990s, the countries took steps that have led to a significant turnaround in economic activity, a drop in inflation, and increases in output, exports and investment. This study describes policy issues that the region continues to face and suggests how the WAEMU countries can address them.